2022
DOI: 10.25026/jsk.v4i4.1320
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Tingkat Pengetahuan dengan Kesediaan Vaksinasi Covid-19 pada Masyarakat di Kabupaten Kutai Kartanegara

Abstract: Virus SARS coronavirus-2 dapat menyebabkan penyakit infeksi COVID-19. Ketika jumlah kasus COVID-19 melonjak, penularan virus corona harus dikendalikan dengan mengikuti berbagai program pemerintah salah satunya vaksin. Adanya pengembangan vaksin COVID-19 ini menimbulkan banyak permasalahan penolakan vaksinasi dikarenakan banyaknya isu hoax mengenai vaksin. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat pengetahuan dengan kesediaan vaksinasi COVID-19 di Kabupaten Kutai Kartanegara karena kuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The low level of public knowledge has a greater impact on the level of public anxiety about the COVID-19 vaccination.The results of this study indicate that the respondents' knowledge of the purpose and benefits of vaccination and their belief that the COVID-19 vaccine is safe includes their willingness to participate in the vaccination program. The respondents' lack of knowledge about the indications and contraindications for using the COVID-19 vaccine is still relatively sufficient (56-75%) [18].Public knowledge about the Covid-19 vaccine is an important aspect to motivate people to actively participate in the vaccine program [19].…”
Section: Discussionmentioning
confidence: 99%
“…The low level of public knowledge has a greater impact on the level of public anxiety about the COVID-19 vaccination.The results of this study indicate that the respondents' knowledge of the purpose and benefits of vaccination and their belief that the COVID-19 vaccine is safe includes their willingness to participate in the vaccination program. The respondents' lack of knowledge about the indications and contraindications for using the COVID-19 vaccine is still relatively sufficient (56-75%) [18].Public knowledge about the Covid-19 vaccine is an important aspect to motivate people to actively participate in the vaccine program [19].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Apriani WD et al 22 found that 90% knew about the COVID-19 vaccine, and 92% were willing to be vaccinated (P = 0.000, r = 0. This shows that there is a relationship between the level of knowledge and willingness to be vaccinated.…”
Section: Originalmentioning
confidence: 99%
“…Tingkat pengetahuan merupakan faktor kesediaan individu melakukan vaksinasi. Hal ini karena semakin tinggi ilmu pengetahuan yang dikuasai, maka semakin luas juga wawasan yang dimiliki mengenai tindakan-tindakan yang perlu dilakukan untuk melakukan program pemerintah, serta memahami manfaat dari dilaksanakannya program vaksinasi itu sendiri untuk menekan angka penyebaran Covid-19 (25) .…”
Section: Hasil Ujiunclassified